2018
DOI: 10.3390/en11030645
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Is a Promising Feedstock for the Synthesis of the Platform Chemical Hydroxymethylfurfural

Abstract: Hydroxymethylfurfural (HMF) has an outstanding position among bio-based platform chemicals, because high-value polymer precursors and fuel additives can be derived from HMF. Unfortunately, the large-scale industrial production of HMF is not yet realized. An open research question is the choice of hexose feedstock material. In this study, we used the highly available disaccharide sucrose for HMF synthesis. The conversion of sucrose was catalyzed by sulfuric acid in water media. Experiments were conducted at tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 43 publications
(88 reference statements)
1
54
0
Order By: Relevance
“…Usually, furfural is generated from pentoses like HMF is generated from hexoses. It is suggested, that small amounts of hexose can form the respective pentose at hydrothermal conditions, which subsequently reacts to furfural …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, furfural is generated from pentoses like HMF is generated from hexoses. It is suggested, that small amounts of hexose can form the respective pentose at hydrothermal conditions, which subsequently reacts to furfural …”
Section: Discussionmentioning
confidence: 99%
“…It is suggested, that small amounts of hexose can form the respective pentose at hydrothermal conditions, which subsequently reacts to furfural. [20,40]…”
Section: Furfuralmentioning
confidence: 99%
“…Energies 2018, 11, x 12 of 15 In addition, the production of levulinic acid (LA) (Figure 4d), which is one of the products of the rehydration of HMF in aqueous media, is observed [61]. Table 5 shows that the addition of acid into the initial slurry produces higher amounts of levulinic acid.…”
Section: Appendix Amentioning
confidence: 98%
“…The twenty-one published papers cover a variety of biomass or waste residuals that have been converted into different types of energy, biofuels or biochemicals including heat [1,11,16], methane [2,4,[7][8][9]17,[19][20][21], electricity [2,11,16], short chain fatty acids [2,19], ethanol [3,12,19], syngas [5,19], nutrient pellets [6], hydroxymethylfurfura [15], and hydrogen [2,10,14,18,19]. The key information including biomass or residuals, products, and technology for the production and type of research are summarized in Table 1.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%
“…Steinbach et al [15] reported a novel process to synthesize hydroxymethylfurfural using highly available disaccharide sucrose as raw material. Hydroxymethylfurfural, as high-value polymer, has unique merits among the bio-based platform chemicals used as precursors and fuel additives.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%